Sealing distal proximal caries lesions in first primary molars: efficacy after 2.5 years (2011)
The prevalence of proximal caries in primary molar teeth is high in many countries. Aims: (1) To study by means of a split-mouth design the 1- and 2.5-year efficacy of sealing proximal lesions vs. flossing instructions (control) on primary molar teeth. (2) To assess children’s behaviour and pain perception during the procedure. Methods: Ninety-one 4- to 6-year-old children from Bogotá, Colombia participated. Participants had to have at least two proximal lesions scored according to the following radiographic classification system: radiolucency (1) in enamel outer half, (2) restricted to enamel-dentine junction, or (3) restricted to dentine outer third. Baseline, 1- and 2.5-year follow-up bitewing radiographs were taken. Test and control lesions were randomly selected. After temporary separation test lesions were sealed (adhesive). Parents/caregivers received a flossing leaflet for their children. Progression of the lesions was assessed by means of independent reading of conventional bitewing radiographs. Results: One-year (n = 73) test vs. control lesion progression was 27.4 vs. 50.7%, respectively (p < 0.01, McNemar’s test), and 2.5-year (n = 56) test vs. control lesion progression was 46.4 vs. 71.4%, respectively (p < 0.01). The dropouts did not differ from those who remained in the study regarding relevant caries baseline data. More than 88% of the participants presented positive to definitively positive behaviour and very low or low pain intensity at both first and second appointments. Conclusion: The sealing technique was superior to flossing instructions both after 1 and 2.5 years of follow-up and the majority of the participants had no anxiety or pain during the treatment.